7.3: Research on LCD display performance improvement based on mini‐LED backlight. (4th October 2019) - Li, Fulin; Qiao, Mingsheng; Li, Hao; Mu, Linjia
Abstract : HDR technology brings higher demands to liquid crystal display terminals ‐ finer local‐dimming control and wider color display range.The Mini‐LED technology is applied to the field of liquid crystal module to increase the number of backlight partitions. This approach can realize not only the thinning of backlight unit, but also more refined dynamic control, improving the dynamic contrast of liquid crystal display. In addition, the quantum dot materials are used as the color conversion materials of the blue Mini‐LED. The combination of Mini‐LED technology and QD technology satisfies the requirements of HDR for liquid crystal display terminals. In this work, by optimizing the matching between luminescence spectrum of the quantum dot light conversion layer and reflection & transmission spectra of the spectral dichroic layer, the brightness of the liquid crystal module using Mini‐LED backlight is increased by more than 20%. At the same time, the chromaticity shift of different display window with local‐dimming control is controlled within 0.015(CIE 1931).